Strategi Marketing Public Relations Kerupuk Seblak Kering UMKM Cilaku Cianjur - Genik Puji Yuhanda; Abdur Razak (KOMVERSAL, 2021)
ABSTRACT This study aims to determine the marketing public relations strategy used by small and medium enterprises to boost image enhancement and product sales revenue. This research uses qualitative research with descriptive analysis method. There is also a research data collection technique conducted by the author is by means of interviews, literature study, observation. The results showed that the marketing public relations strategy had a positive impact. This is indicated by the consistent marketing of products from warung to warung (push). The pull technique has also been carried out by utilizing online media (shopee) marked by an increase in sales turnover in the August-November 2020 period when compared to 2019 revenue in the same month range. There is also social media that is used in marketing seblak dry cracker products, namely by using Facebook and Shopee accounts. The impact of research can become a reference experience for similar businesses as well as new knowledge about push and pull strategies in public relations marketing strategies. Keywords: Marketing public relations, strategy push, pull, pass, MSME ABSTRAK Penelitian ini bertujuan mengetahui strategi marketing public relations yang digunakan oleh usaha kecil menengah untuk mendongkrak peningkatan citra dan pendapatan penjualan produk. Penelitian ini menggunakan jenis penelitian kualitatif dengan metode deskriptif analisis. Ada pun teknik pengumpulan data penelitian yang dilakukan penulis adalah dengan cara wawancara, studi literatur, observasi. Hasil penelitian menunjukkan bahwa strategi marketing public relations berdampak positif. Hal itu ditandai dengan pemasaran produk yang dilakukan secara konsisten dari warung ke warung (push). Teknik pull juga telah dilakukan dengan memanfaatkan media online (shopee) ditandai dengan peningkatan omzet penjualan pada periode Agustus-November 2020 jika dibandingkan pendapatan 2019 pada rentang bulan yang sama. Ada pun media sosial yang digunakan dalam memasarkan produk kerupuk seblak kering yaitu dengan memanfaatkan akun facebook dan shopee. Dampak penelitian bisa menjadi rujukan pengalaman bagi usaha sejenis juga ilmu baru tentang strategi push dan pull dalam strategi marketing public relations. Kata kunci: Marketing public relations, strategi push, pull, pass, UMKM